Smart Dining Operations : An Integrated Digital Approach - Dr. Shilpi Jain,; Dr. Madhur Jain,; Rupal Malhotra,; Mahaprasad Dehury,; Himanshu Rawat,; Deepanshu Baluni, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Efficient canteen management is essential to enhancing the food service experience in educational and institutional environments, impacting both user satisfaction and operational efficiency. Traditional methods for managing orders, inventory, and customer feedback are often manual, leading to delays, errors, and resource inefficiencies. This project introduces SnapMeal, a comprehensive, web-based canteen management system, developed to streamline canteen operations while offering a seamless experience for users and administrators. Built using the MERN stack (MongoDB, Express.js, React.js, Node.js), SnapMeal offers features including a user dashboard, real-time menu browsing, order placement, payment integration, and an admin panel for managing inventory and order tracking. By automating key processes and centralising canteen management, SnapMeal enhances efficiency, reduces wait times, and provides a more satisfying experience for users. This scalable and adaptable platform aims to support institutional needs by leveraging technology to improve order processing, inventory management, and customer engagement.
Keywords: Canteen Management; Web Application; MERN Stack; MongoDB; React.js; Efficiency; Real-Time Order Processing; Inventory Management